Efficacy of adjunctive autologous serum in the comprehensive treatment of bacterial corneal ulcers in patients with diabetic mellitus - O. V. Zavoloka; P. A. Bezditko (Ukrainian Society of Ophthalmologists, 2020)
Background: The presence of diabetic keratopathy associated with diabetic corneal neuropathy should be taken into account in the management of corneal inflammation in patients with diabetes mellitus. Purpose: To determine the impact of adjunctive topical autologous serum eye drops on delayed healing of bacterial corneal ulcers in patients with type 1 diabetes mellitus (DM1). Material and Methods: We retrospectively reviewed the results of observing 19 DM1 patients (19 eyes) with bacterial corneal ulcers who exhibited delayed healing of corneal ulceration and whose corneal smears and scrapings taken one week after initiation of treatment were bacteriologically negative. Patients had a routine eye examination (visual acuity, tonometry, and slit-lamp biomicroscopy of anterior and posterior eye segments), bacteriological studies, fluorescein dye test, anterior eye OCT and non-contact corneal esthesiometry. Patients of the control group (9 individuals) continued receiving only background therapy (topical antiseptics, antioxidants, repairing agents, artificial tears, and mydriatics and systemic anti-inflammatory agents), whereas patients of the main group began receiving autologous serum eye drops in addition to background therapy of topical antiseptics, mydriatics and systemic anti-inflammatory agents. Clinical picture data for day 1 (visit 1, before administering the treatment) and days 7 (when corneal samples and scrapings were re-taken), 14 (when bacteriology results became available and main group patients were additionally administered autologous serum), 17, 21 and 24 were analyzed. Results: In DM1 patients with delayed healing of bacterial corneal ulcers, the use of adjunctive autologous serum eye drops after eradication of the offending microorganisms resulted in reductions in precorneal injection and size and depth of the ulcer defect and complete resolution of corneal infiltration and edema of the corneal tissue surrounding the ulcer as early as day 3, and recovery of all patients and a 32.6% improvement in corneal sensitivity on day 10. Conclusion: Using adjunctive topical autologous serum eye drops after eradication of the offending microorganisms was found to be efficacious in the comprehensive treatment of delayed healing of bacterial corneal ulcers in patients with DM1.